Green preparation of fluorescent carbon dots from lychee seeds and their application for the selective detection of methylene blue and imaging in living cells1. Issue 33 (7th September 2015) - Xue, Mingyue; Zou, Mengbing; Zhao, Jingjin; Zhan, Zhihua; Zhao, Shulin
<x xml:space="preserve">Abstract</x> A green approach was developed for the preparation of fluorescent carbon dots (CDs) by using lychee seeds as precursors, and the CDs were employed as fluorescence probes for the detection of methylene blue and imaging in living cells.